Evaluating the in vitro anti-Leishmanial activity of essential oil extracted from Cymbopogon Citratus against Leishmania Donovani - Abdullah, Mahmmoud Shakir; Alqaisi, Amjed Qays Ibrahim (Iraqi Journal of Science, 2022)
Leishmania is one of the protozoan parasites that are transferred to human by infected sand flies and gives rise to a range of diseases entitled as Leishmaniasis. More than 20 known species of Leishmania can infect humans and cause various clinical symptoms. Three most known clinical manifestations are Cutaneous Leishmaniasis (CL), Mucocutaneous Leishmaniasis (MCL) and Visceral Leishmaniasis (VL) (kala-azar or black fever). The difference in the clinical form dependent on several factors: species of Leishmania, type of vector that transmits the Leishmania, and the immune status of an infected individual. The current drugs which are used as anti-leishaminial treatment are characterized by enormous side effects, including their toxicity to human, long term treatment, liver problems and huge cost. Therefore, there is a necessity to find an alternative treatment marked as low cost, more specific against parasite’s stages, and metabolic pathways, and non-toxicity to human. Plants are considered one of the important sources for the remedy of the tropical diseases caused by bacteria, viruses, and parasites. Cymbopogon Citratus (lemon grass) is a herbal medicine used as anti-inflammatory, antibacterial, antifungal, anti-malarial, anti-protozoal and for gastrointestinal problems remedy. In order to detect the effects of C. Citratus against Leishmaniasis, in this study, serial dilution for the essential oil of C.citratus (1000, 500, 250, 125, 62.5 and 31.25) µg/ml were used against L. donovani Promastigotes. Viability was also evaluated at 24, 48 and 72 hours post-treatment. The results revealed that high concentrations (1000, 500 and 250) µg/ml were more effective than other concentrations during all time intervals, and IC50 values were 640, 492 and 442 µg/ml at 24, 48 and 72 hours respectively. In conclusion, this current study is one of a persistent search to find new treatments characterized by its high activity and low adverse effects to treat protozoa parasites for instance, Leishmania, and displays the effectiveness of the essential oils as a promising alternative